اتجاهات الناخبين الأردنيين نحو قانون الإدارة المحلية رقم "25" لسنة 2021 الجديد - المشاقبة، باسل سالم عبود (جامعة آل البيت, 2023)
هدفت هذه الدراسة إلى الكشف عن اتجاهات الناخبين الأردنيين نحو قانون الإدارة المحلية رقم (٢٥) لسنة ۲۰۲۱ الجديد، ولتحقيق هذا الهدف تم اختار عينة عشوائية ممن يحق لهم الانتخاب بموجب هذا القانون وسبق لهم الاطلاع عليه بلغت (۱۷۳) من مختلف محافظات الأردن، كما تم بناء مقياس للاتجاهات تكون من الخصائص الديمغرافية، بالمشاركة أو عدم المشاركة في انتخابات اللامركزية السابقة، مصدر الاطلاع على قانون الإدارة المحلية رقم (٢٥) لسنة ۲۰۲۱ الجديد، أسباب الاطلاع على قانون الإدارة المحلية رقم (٢٥) لسنة ۲۰۲۱ الجديد) كما تضمن المقياس (۱۹) فقرة موزعة على ثلاثة مجالات هي الاتجاهات نحو أسلوب تشكيل مجالس اللامركزية في قانون الإدارة المحلية الجديد، ولاتجاهات نحو صلاحيات مجالس اللامركزية في قانون الإدارة المحلية الجديد وله (۷) فقرات والاتجاهات نحو المشاركة في انتخابات اللامركزية القادمة في ظل في قانون الإدارة المحلية الجديد. وبعد التأكد من صدقة وثباته تم تطبيقه على أفراد العينة حيث أظهرت النتائج أن اتجاهات الناخبين الأردنيين نحو قانون الإدارة المحلية رقم (٢٥) لسنة ۲۰۲۱ الجديد تراوحت بين متوسطة وقليلة، كما أظهرت النتائج عدم فروق ذات دلالة إحصائية تعزى لمتغيرات النوع الاجتماعي، العمر، المؤهل العلمي، الوظيفة الحالية، مكان السكن الاتجاه السياسي. وفي ضوء تلك النتائج خرجت الدراسات بمجموعة من التوصيات من أهمها إعادة النظر في قانون الإدارة المحلية الجديد من خلال تضمنه إدراج صلاحيات فعلية توفر للمجالس فرص القيام بعمليات التنمية بشكل أكثر فعالية. This study aimed to reveal the attitudes of Jordanian voters towards the new Local Administration Law No. (25) for the year 2021, and to achieve this goal, a random sample of those entitled to vote under this law were selected and had previously seen the law, amounting to (173) from different governorates of Jordan. A measurement of attitudes out from demographic characteristics was built, whether or not to participate in the previous decentralization elections, the source of reviewing the new Local Administration Law No. (25) for the year 2021, the reasons for reviewing the new Local Administration Law No. (25) of 2021) and the scale also included (19) items divided into three areas: Trends towards the method of forming decentralization councils in the new local administration law, and trends toward the powers of decentralization councils in the new local administration law that has (7) items, and trends toward participating in the upcoming decentralization elections in light of the new local administration law. After verifying its validity and reliability, it was applied to the sample members, where the results showed that the attitudes of Jordanian voters towards the new Local Administration Law No. (25) for the year 2021 ranged between medium and few. The results also showed no statistically significant differences due to the variables of gender, age, and educational qualification, current job, place of residence, and political orientation. In light of these results, the studies came out with a set of recommendations, the most important of which is to reconsider the new local administration law through its including the inclusion of actual powers that provide councils with opportunities to carry out development operations more effectively.
Keywords: الاتجاهات السياسية -- الانتخابات اللامركزية -- النصوص القانونية -- الإدارة المحلية -- الأردن